Global Citizenship Education in a Local Context: Building Cross-Cultural Competency through Islamic Religious Education - Malik, Muhammad Umar Ibnu; Milah, Asep Dhoni Syaiful; Syibromalisi, Alwi Akhmad; Daimah, Kholisoh; Fazriyah, Siti (Proceedings Series on Social Sciences & Humanities, 2025)
Peacebuilding through education toward global citizenship is one of the essential pillars in realizing the United Nations 2030 Agenda for Sustainable Development. In this framework, the topic directly relates to Sustainable Development Goal (SDG) 4.7, which encourages education for sustainable development, global citizenship, a culture of peace, and non-violence. Global Citizenship Education (GCED) plays a strategic role in promoting peace by fostering the ability to think globally and act locally. This includes integrating emotional intelligence (EQ), cultivating shared values, mitigating climate change, and promoting gender equality as key indicators in shaping decision-making processes and institutional structures. These elements reflect civic engagement at both local and global levels through the triptych approach: foundation, adaptation, and integration. Implementing GCED within diverse local contexts, especially in multicultural and religiously plural environments like Indonesia, requires tailored strategies. In this regard, Islamic Religious Education (PAI) has significant potential as a foundation for fostering cross-cultural competencies among students. This article explores how Islamic Religious Education can construct students' cross-cultural competencies through curriculum development based on GCED principles while remaining rooted in Indonesia's socio-religious context. Using a qualitative literature review, this study critically examines how PAI can be a strategic entry point for integrating GCED in Indonesian education without compromising local identity and religious values. The findings indicate that integrating GCED into PAI faces various challenges, particularly teachers' limited understanding of GCED and the absence of a curriculum responsive to global issues. Therefore, an effective strategy is needed, including innovative curriculum design, project-based learning models, intercultural dialogue, and enhancing teachers' roles as facilitators who connect Islamic values with global citizenship awareness.